Mapping Business Model Strategy Based-On Motivation of People to Participating in Sharing Economy - Zuhri, Wahyu; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2021)
The sharing economy is a growing concept that has a massive and positive impact on society, but it is still below the traditional economy. This study is purposed mapping of sharing economy companies in Indonesia and international, and also to identify how their revenue stream, channel, and customer relationship strategy of pioneer sharing economy companies in response to motivation theory as an effort to provide literature and references for other existing or potential sharing economies, so that is expected to accelerate the development of the sharing economy. This research uses a qualitative approach and secondary data collected from previous research, company website, and articles. In this research, sharing economy companies determination is conducted by sort list of companies collected from the article based on requirements or indicators of sharing economy and pioneer sharing economy companies determination conduct use Alexa traffic and Simillarweb by comparing their rank as an indication of success in encouraging people to participate. Revenue stream assessment by looking at their revenue stream type and their monetization strategy. Channel and customer relationships assess by looking at their website using indicators of motivation (Economy Benefit, convenience, Sustainability, Sense of belonging, and Trust) to see the initiative. As the result of this research, 1. List of sharing economy companies in Indonesia and internationally divided into six sectors (finance, space, transportation, services, food, & goods) but in Indonesia, there is no company engaged in the food sector that meets the definition of the entire sharing economy. 2) List of revenue stream model strategies and monetizing strategies of sharing economy companies. In terms of revenue stream model strategy, it is found that the pattern is that companies charge commission fees to providers and assign transaction fees to users. 3)mapping website companies initiative as one of channel and customer relationship strategy in response to motivation theory, it is found the pattern in each sector and in general, it’s pattern means all companies have the initiative in some indicators. This research can be a standard or reference of other existing or potential sharing economy companies in determining business model strategy as an effort to accelerate the development of the sharing economy.Keywords: Sharing economy, Motivation, Business mode